1994
DOI: 10.1177/000348949410300807
|View full text |Cite
|
Sign up to set email alerts
|

Osteoma of the Internal Auditory Canal Case Report and Literature Review

Abstract: Osteomas of the internal auditory canal are rare lesions, with only 12 reported cases in the world literature. Symptoms are those of eighth nerve compression, and include unilateral hearing loss and vestibular weakness, thus mimicking symptoms of acoustic neuroma. We report a patient with an osteoma of the internal auditory canal, along with a review of the literature. We note age and sex characteristics from the literature, give evidence of localized trauma as a possible etiologic factor for this lesion, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…Six cases were identified incidentally (12%), including our case which was asymptomatic in the affected side at detection, 7 cases had subjective or objective hearing loss (41%), 10 cases had tinnitus and/or aural fullness of the affected side (59%), 11 cases had vertigo and/or dizziness (including past medical history) (65%), and 2 cases had facial palsy (including past medical history) (12%). Several causes have been proposed for IAC osteoma, such as trauma, infection, inflammation, hormones, and constant vascular irritation (Clerico et al 1994;Wright et al 1996;Baik et al 2011), but no apparent risk factors were observed in this review. These results suggest that the rate of incidentally diagnosed cases continues to be high, the predilection for postmenopausal women is not so remarkable, and the risk factors for IAC osteoma remain unclear.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Six cases were identified incidentally (12%), including our case which was asymptomatic in the affected side at detection, 7 cases had subjective or objective hearing loss (41%), 10 cases had tinnitus and/or aural fullness of the affected side (59%), 11 cases had vertigo and/or dizziness (including past medical history) (65%), and 2 cases had facial palsy (including past medical history) (12%). Several causes have been proposed for IAC osteoma, such as trauma, infection, inflammation, hormones, and constant vascular irritation (Clerico et al 1994;Wright et al 1996;Baik et al 2011), but no apparent risk factors were observed in this review. These results suggest that the rate of incidentally diagnosed cases continues to be high, the predilection for postmenopausal women is not so remarkable, and the risk factors for IAC osteoma remain unclear.…”
Section: Discussionmentioning
confidence: 74%
“…A previous review of 13 cases of IAC osteoma reported from 1882 to 1993 identified several clinical characteristics as follows: mean age of 57 years; female-to-male ratio of 5.5:1, suggesting a particular predilection for postmenopausal women; and 42% of the patients had no symptoms, 42% had hearing loss, 25% had tinnitus, and 33% had vertigo (Clerico et al 1994). Our present study summarized and reviewed 17 cases of IAC osteoma reported in the past 22 years (1992-2013) (Singh et al 1992;Ramsay and Brackmann 1994;Coakley et al 1996;Wright et al 1996;Boedts et al 1997;Davis et al 2000;Vrabec et al 2000;Kovacić et al 2001;Gerganov et al 2008;Liétin et al 2010;Baik et al 2011;Kaymakci et al 2012;Plantone et al 2013) and excluded the previously reviewed cases by Clerico et al (1994) (Table 1). Mean age was 44.1 years (male: 44.0, female: 44.2), and femaleto-male ratio was 1.4:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IAC stenosis is classified into acquired bony disease [1][2][3] , 5]. There is no evidence to support the hypothesis that IAC stenosis can occur as an acquired disorder in the absence of specific focal or diffuse bony disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…This method of diagnosis is available for 4 reported osteomas. [9][10][11][12] alone. 13,14 Two cases are reported based on radiographic appearance alone.…”
mentioning
confidence: 99%